Perceived Communication Effectiveness among Researchers, Extension personnel and Farmers - 0. Sarada; K. Prabhakar; M. Sudarshan Reddy (Journal of Agricultural Extension Management, 2025)
In the development of agriculture particularly in countries like Indi a where about 65 per cent of the population depends on agriculture, communication plays a significant role in transfer of technology. Agricultural progress in any country depends upon spread of reliable, pragmatic and accurate information related to recommend improved practices to the tillers of the soil. To create awareness and awakening, it is essential that the message is communicated regularly, effectively and efficiently with the support of media to the clientele group. Acceptance of information and ide as by receivers is based on "who said it" and how they perceive the communication source. Personal, psychological and communication characters of extension personnel and farmers are the important fac tors influencing their perceived communication effectiveness of researchers and ex tension personnel. Hence the present study was undertaken to study the perceived communication effectiveness among researchers, extensionists and farmers and to find out the influence of selected factors on perceived communication effectiveness